ANALISIS KEBUTUHAN LITERASI SOSIAL BUDAYA TERHADAP PERKEMBANGAN AKHLAK SISWA - Nurmawati Nurmawati (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
Education is currently expected to be able to produce human resources who have strong communication and collaboration skills, are experts in the use of technology, think creatively and innovatively, and are able to solve all the problems faced in life. One of the things that schools and madrasas must achieve in today's 21st-century education is skills. This study aims to analyze the need for socio-cultural literacy assessment by utilizing social care content and local cultural participation. The results of this needs analysis will be used as a basis for developing socio-cultural literacy instruments in learning aqidah morals. This type of research is descriptive research. Respondents in this study were 80 students of class VIII MTs Yapila Langsa. Data collection was carried out in November 2022. The data collection method used was a questionnaire, which included a questionnaire analyzing the needs of socio-cultural literacy in learning aqidah morals. The needs analysis questionnaire is in the form of an open questionnaire using social care content text and local cultural participation. The data obtained from the questionnaire were then analyzed descriptively. Needs analysis is based on domain analysis. The indicators and aspects that are used as benchmarks for obtaining this needs analysis data are, (1) intellectual skills (2) social sensitivity, ability to control oneself (3) cooperative skills (4) attitudes and social values and (5) ability participate in the local cultural environment.